2013
DOI: 10.4314/ahs.v13i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Living with parents and risky sexual behaviors among preparatory school students in Jimma zone, South west Ethiopia

Abstract: Background: Risky sexual behavior is any behavior that increases the probability of negative consequences associated with sexual contact. Family environment, peer influence, community factors and school attachment seem an important factor affecting sexual risk behavior and decision of in-school youths. Objective: To assess sexual risk behaviors and associated factors among students living with parents in Jimma zone preparatory schools. Methods: A cross sectional study designs both qualitative and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 18 publications
7
41
3
3
Order By: Relevance
“…The finding was in line with a study conducted among preparatory students in Jimma Zone where the lifetime RSB was 42.1% [28]. However, it was higher than studies conducted among high school students in Humera and Gondar, North West Ethiopia where lifetime RSB were 13.7 and 25% respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The finding was in line with a study conducted among preparatory students in Jimma Zone where the lifetime RSB was 42.1% [28]. However, it was higher than studies conducted among high school students in Humera and Gondar, North West Ethiopia where lifetime RSB were 13.7 and 25% respectively.…”
Section: Discussionsupporting
confidence: 88%
“…This implies that BCC should be strengthened among college adolescents/youths on substance use and its consequences together with regulatory mechanisms in the use of substances. However, the finding was not consistent with studies conducted in Jimma and Bahir Dar that revealed no association between khat chewing and RSB [6, 28]. Similarly, findings from Humera and Addis Ababa revealed that there was no association between smoking cigarette, khat chewing and alcohol drinking and RSB.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Factors that have shown to support the use of condoms include family support and connection, strong relationships with teachers and other students, discussions about sexuality with friends and peers, higher perceived economic status, and higher levels of education [5–7]. Risk factors associated with non-use of condoms or other risky sexual behaviors include low involvement in religious activities, high levels of alcohol consumption, and poor knowledge of HIV/AIDS [5, 8]. Thus, there is a need to focus on increasing use of condoms among young men, for the prevention of HIV, STIs, and unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was different with the study conducted by Abebe et al (2014) in Jimma zone, South west Ethiopia. Which were (42%) students had sexual behavior (34). Another study also conducted by Guttmacher Institute in USA (2011) found that current data from USA showed that 46% of in-school youths had ever had sexual intercourse (35).…”
Section: Discussionmentioning
confidence: 99%